The ethics of power: a comparative analysis of Nietzsche's will to power and Spinoza's Conatus - Çal, Hasan Cem (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: The similarities between Spinoza’s philosophy and Nietzsche’s have long been debated. While there are many differences between Spinoza’s philosophy and Nietzsche’s, it can also be said that there are many similarities. For example, the fact that both philosophers have a philosophical understanding based on immanence, that they both prioritize ethics rather than morality, and that they both give priority to emotions in their philosophy, in a way, defines some of these similarities. Although Nietzsche was very critical of Spinoza, it still seems possible to link Spinoza’s philosophy with Nietzsche’s. Perhaps the most striking similarity between Spinoza and Nietzsche in philosophical terms reveals itself in the basic concepts that constitute a central place in their philosophies of immanence. These concepts are the will to power in Nietzsche and conatus in Spinoza. These two rather foundational concepts seem to form the basis of the theoretical affinity between Spinoza and Nietzsche because both give a similar meaning and context to his concept and place his concept at the base of his philosophical activity. This thesis, in its entirety, aims to examine the similarity between the concepts of the will to power and conatus, and to underline Nietzsche and Spinoza’s philosophical convergence through a comparative analysis of these concepts.

ÖZET: Spinoza’nın felsefesiyle Nietzsche’ninki arasındaki benzerlikler uzunca bir süredir tartışılagelmiştir. Spinoza’nın felsefesiyle Nietzsche’ninki arasında birçok farklılık olsa da, aynı zamanda birçok benzerlik de bulunduğu söylenebilir. Her iki felsefecinin de içkinliği temel alan felsefi bir anlayışa sahip olması, her ikisinin de ahlaktan ziyade etiği ön planda tutması ve yine her ikisinin de felsefesinde duygulara öncelikli bir yer vermesi, örneğin, bir bakıma bu benzerlikleri tanımlar niteliktedir. Her ne kadar Nietzsche Spinoza’ya bir hayli eleştirel yaklaşmış olsa da, Spinoza’nın felsefesiyle Nietzsche’ninki arasında bağlantı kurmak yine de mümkün gözükür. Nietzsche ve Spinoza arasında felsefi açıdan en göze çarpan benzerlik ise muhtemelen onların içkinlik felsefelerinde merkezi bir yer teşkil eden temel kavramlarda kendisini açığa vurur. Bu kavramlar, Nietzsche’de güç istenci, Spinoza’da ise conatus’tur. Bu iki kurucu nitelikteki kavram, Nietzsche ve Spinoza arasındaki teorik yakınlığın temelini oluşturur gibidir; çünkü her ikisi de kendi kavramına benzer bir anlam ve bağlam verir ve bu kavramı kendi felsefi faaliyetinin temeline yerleştirir. Bütünlüğünde bu tezin amacı, güç istenci ve conatus kavramları arasındaki benzerliği incelemek ve bu kavramların karşılaştırmalı bir analizi aracılığıyla Nietzsche ve Spinoza arasındaki felsefi yakınsamanın altını çizmektir.
Güç etiği: Nietzsche"nin güç istenci ve Spinoza"nın Conatus'unun karşılaştırmalı bir analizi
Keywords: The Will to Power; Conatus; The Self; The Ethical Self; Ethics; Güç İstenci; Conatus; Kendilik; Etik Kendilik; Etik